Solid State Kinetics and Antimicrobial Studies for Copper (II) Sesame and Copper (II) Groundnut Complexes with Substituted Benzothiazole Ligand - Meena, Asha; Sukhadia, Vandana; Sharma, Rashmi (Letters in Organic Chemistry, 2021)
The aim of this manuscript is to give an overview of new findings in the field of thermal degradation and antimicrobial studies for copper (II) sesame and copper (II) groundnut complexes with substituted benzothiazole ligand. Solid state kinetics and thermal degradation have gained the attention of the scientific community not only due to their numerous applications in environment, energy, wastewater treatment, pollution control and green chemistry but also due to their wide range of biological activities. This work aims to explore the study of chemical steps of the investigated degradation and the evaluation of the kinetic and thermodynamic parameters of the newly synthesized biologically active complexes (CSBe and CGBe) derived from two different edible oils, i.e., sesame and groundnut and ligand containing nitrogen, oxygen and sulphur atoms, i.e., 2-amino-6-ethoxy benzothiazole. The studies include Coats-Redfern equation (CRE), Horowitz-Metzger equation (HME), Broido equation (BE) and Piloyan-Novikova equation (PNE) for the analysis of the degradation and energetics for each step using kinetic data. The observation suggests that CGBe takes a longer time and higher temperature to decompose completely than CSBe. Antimicrobial activities against Staphylococcus aureus of these compounds have also been analysed which may provide an important account of information about their industrial utilization. The TGA study reveals that CSBe and CGBe complexes undergo stepwise thermal degradation of the ligand-soap bond of complex and saturated and unsaturated fatty acid components of edible oils, i.e., sesame and groundnut. The order of antimicrobial activities of the two complexes studied is – CSBe > CGBe. These results reveal that the nature of different nitrogen, oxygen and sulphur containing ligands coordinated with copper ion plays a significant role in the inhibition activity.
Keywords: kinetic parameters